The BRCA1 alternative splicing variant Δ14-15 with an in-frame deletion of part of the regulatory serine-containing domain (SCD) impairs the DNA repair capacity in MCF-7 cells - Sevcik, Jan; Falk, Martin; Kleiblova, Petra; Lhota, Filip; Stefancikova, Lenka; Janatova, Marketa; Weiterova, Lenka; Lukasova, Emilie; Kozubek, Stanislav; Pohlreich, Petr; Kleibl, Zdenek (Cellular signalling, 2012)
The BRCA1 gene codes for a protein involved in the DNA double strand break (DDSB) repair. Alongside the dominant full-length splicing form of BRCA1, numerous endogenously expressed alternative splicing variants of unknown significance have been described in various tissues. Some of them retain the original BRCA1 reading frame but lack several critical BRCA1 structural domains, suggesting an altered function of the resulting protein in the BRCA1-regulated processes. To characterize the effect of the BRCA1Δ14-15 splicing variant (with an in-frame deletion affecting the regulatory serine-containing domain) on the DDSB repair, we constructed the MCF-7 clones stably expressing the analyzed variant with/without a shRNA-mediated downregulation of the endogenous full-length wild-type BRCA1 expression. Our results show that the expression of the BRCA1Δ14-15 variant delays the γ-radiation-induced DDSB repair, alters the kinetics of irradiation-induced foci formation/decomposition and reduces the non-homologous end-joining capacity in MCF-7 cells. Therefore, the BRCA1Δ14-15 is not able to functionally replace the full-length wt BRCA1 in the DDSB repair. Our findings indicate that the endogenously expressed BRCA1 alternative splicing variants may negatively influence genome stability and support the growing evidence of the pathological potential of the sequence variants generated by an altered or misregulated alternative splicing in the process of mammary malignant transformation.
Keywords: záření gama; sekvenční delece; nádory prsu; Base Sequence; Gamma Rays; Female; Reading Frames; Cell Line, Tumor; Protein Structure, Tertiary; ženské pohlaví; BRCA1 Protein; sekvence aminokyselin; terciární struktura proteinů; lidé; Cell Nucleus; DNA End-Joining Repair; Molecular Sequence Data; Breast Neoplasms; oprava DNA spojením konců; Amino Acid Sequence; DNA Breaks, Double-Stranded; čtecí rámce; buněčné jádro; molekulární sekvence - údaje; protein BRCA1; Protein Isoforms; dvouřetězcové zlomy DNA; sekvence nukleotidů; Gene Expression; exprese genu; protein - isoformy; Sequence Deletion; nádorové buněčné linie; Humans